Urinary Bacterial Profile and Antibiotic Susceptibility Pattern among Pregnant Women in Eastern Libya - Elabbar, Fatma; Elgtani, Wala; Bodalal, Fida; Mansur, Khadiga; Elzahaf, Raga (AlQalam Journal of Medical and Applied Sciences, 2024)
Urinary tract infections, which affect approximately 20% of pregnancies globally, particularly in developing nations with high birth rates like Libya, are a public health concern that complicate pregnancy and are linked to catastrophic maternal, fetal, and neonatal outcomes. Choosing an appropriate therapy depends on current understanding about antibiotics, which is essential for early issue detection and prevention. In this study, antenatal care clinics in several eastern Libyan cities, including "Benghazi, Almarj, Albayda, Shahat, Darna, Alquoba," participated in a cross-sectional investigation to identify the most common causes of UTIs and to ascertain the sensitivity and resistance of antibiotic patterns. From February 9 to April 15, 377 samples were gathered utilizing a standardized questionnaire to obtain data. UTI was diagnosed using mid-stream urine culture on standard culture media. Out of the 377 pregnant women who were included, E. Coli had the greatest infection rate (43.0%), followed by Klebsiella pneumonia (10.3%), Staphylococcus aureus (16.4%), and Staphylococcus saprophyticus (11.4%). The most effective antibiotics were found to be Augmentin (58.9%), Ciprofloxacin (52.6%), and Nitrofurantoin (51.3%), although Azithromycin and Nalidixic acid showed strong resistance to most uropathogens. Our research reveals that urinary tract infections (UTIs) are prevalent among pregnant women in eastern Libya and that bacteria that are extremely resistant to most tested antibiotics are appearing more frequently. These results should cause doctors to reevaluate their treatment strategies in light of antibiotic susceptibility data. تعد عدوى المسالك البولية، التي تؤثر على ما يقرب من 20٪ من حالات الحمل على مستوى العالم، وخاصة في الدول النامية ذات معدلات المواليد المرتفعة مثل ليبيا، مصدر قلق للصحة العامة يعقد الحمل ويرتبط بنتائج كارثية للأم والجنين والوليد. يعتمد اختيار العلاج المناسب على الفهم الحالي للمضادات الحيوية، وهو أمر ضروري للكشف المبكر عن المشكلة والوقاية منها. في هذه الدراسة، شاركت عيادات رعاية ما قبل الولادة في عدة مدن شرق ليبيا، بما في ذلك "بنغازي، المرج، البيضاء، شحات، درنة، القبة"، في تحقيق مقطعي لتحديد الأسباب الأكثر شيوعًا لالتهابات المسالك البولية والتأكد من حساسية ومقاومة أنماط المضادات الحيوية. من 9 فبراير إلى 15 أبريل، تم جمع 377 عينة باستخدام استبيان موحد للحصول على البيانات. تم تشخيص التهاب المسالك البولية باستخدام مزرعة منتصف مجرى البول على وسائط زراعة قياسية. من بين 377 امرأة حامل تم تضمينهن، كان معدل الإصابة بـ E. Coli هو الأعلى (43.0٪)، تليها Klebsiella pneumonia (10.3٪)، Staphylococcus aureus (16.4٪)، و Staphylococcus saprophyticus (11.4٪). وقد تبين أن أكثر المضادات الحيوية فعالية هي أوغمنتين (58.9%)، وسيبروفلوكساسين (52.6%)، ونيتروفورانتوين (51.3%)، على الرغم من أن أزيثروميسين وحمض الناليديكسيك أظهرا مقاومة قوية لمعظم مسببات الأمراض البولية. وتكشف أبحاثنا أن التهابات المسالك البولية منتشرة بين النساء الحوامل في شرق ليبيا وأن البكتيريا شديدة المقاومة لمعظم المضادات الحيوية المختبرة تظهر بشكل متكرر. وينبغي أن تدفع هذه النتائج الأطباء إلى إعادة تقييم استراتيجيات علاجهم في ضوء بيانات حساسية المضادات الحيوية.